100 most-cited articles on diabetic retinopathy - Koh, Barry Moses Quan Ren; Banu, Riswana; Nusinovici, Simon; Sabanayagam, Charumathi (British journal of ophthalmology, 2021)
Diabetic retinopathy (DR) research has had significant advancements over the past decades. We analysed the impact and characteristics of the top 100 (T100) most-cited articles in DR research. The Scopus database was searched for articles published from 1960 to June 2020 by two independent investigators. The T100 DR articles were published between 1961 and 2017 with median citations of 503 (range: 306–20 100); 84% were published after 1990. More than half (59%) were published in general medical/diabetes journals while 37% in ophthalmology journals. The top six journals contributed to 56% of the T100: Ophthalmology (n=13), Archives of Ophthalmology (n=12), Diabetes (n=9), New England Journal of Medicine (n=8), Journal of the American Medical Association (n=7) and The Lancet (n=7). Although observational studies were most popular (33%), randomised controlled trials (RCTs, 24%) published in journals with higher impact factor (IF) and citations (median IF and citations=7.113, 503 vs 21.437, 696.5, both p-value<0.05). 33 of the T100 were cited by several international DR clinical guidelines. The USA contributed to 63% of T100, but 18% of articles published after 2000 came from Asia. More than 80% of both first and last authors were men. Artificial intelligence (AI) to screen for DR ranked 14th and 99th despite recent publications in 2016 and 2017, respectively. To conclude, our T100 analysis showed that RCTs were most-cited and more articles were published in non-ophthalmology than ophthalmology journals. It highlights the impact the T100 DR has in shaping guidelines used to date in DR management, identifies AI for DR screening as an emerging area and shows a contemporary rise of Asian contribution in DR research.